2015
DOI: 10.1111/jpg.12620
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum Geology and Hydrocarbon Potential of the Guban Basin, Northern Somaliland

Abstract: The Guban Basin is a NW-SE trending Mesozoic-Tertiary rift basin located in northern Somaliland (NW Somalia) at the southern coast of the Gulf of Aden. Only seven exploration wells have been drilled in the basin, making it one of the least explored basins in the Horn of Africa --southern Arabia region. Most of these wells encountered source, reservoir and seal rocks. However, the wells were based on poorly understood subsurface geology and were located in complex structural areas.The Guban Basin is composed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 22 publications
(33 reference statements)
2
26
0
Order By: Relevance
“…15a). The group correlates well with other Gulf of Aden depocentres in northern Somalia, such as those in the Daban Basin (Ali, 2015). Deposition of the Nogal Group was controlled by growth faults related to the development of the Gulf of Aden rifting event (Figs 9-11).…”
Section: Tectonic Evolution Of the Nogal Basinsupporting
confidence: 56%
See 1 more Smart Citation
“…15a). The group correlates well with other Gulf of Aden depocentres in northern Somalia, such as those in the Daban Basin (Ali, 2015). Deposition of the Nogal Group was controlled by growth faults related to the development of the Gulf of Aden rifting event (Figs 9-11).…”
Section: Tectonic Evolution Of the Nogal Basinsupporting
confidence: 56%
“…They showed that basin fills in general can be divided into five stratigraphic sequences that range in age from Late Jurassic to Neogene. In addition, Ali (2015) investigated the petroleum geology and hydrocarbon potential of the Mesozoic-Neogene Guban rift basin, which is located along the southern coast of the Gulf of Aden and NW of the Nogal Basin.…”
Section: Introductionmentioning
confidence: 99%
“…Source rock analyses made on samples from the Nogal-1, Kalis-1, Faro Hills-1, Las Anod-1, Burhisso-1 and Buran-1 wells ( Table 2) were used as input for the petroleum systems modelling. In addition, source rock properties measured from Upper Jurassic outcrops in the Guban Basin were used as input for the Bihendula source model (Ali, 2006;Ali, 2015). PetroMod petroleum systems modelling software was used to simulate the generation, migration and accumulation of hydrocarbons in the basin.…”
Section: Methodsmentioning
confidence: 99%
“…The basin is bounded by the escarpment of the northern Somalia plateau to the south and by the Gulf of Aden in the north. The study concluded that mature source rocks of Late Jurassic age (Gahodleh and Daghani shales) together with various reservoir rocks are present in the basin (Ali, 2015). Furthermore, Ali and Watts (2016) reported that the sedimentary succession of the Guban Basin is similar to that in the Nogal Basin (Fig.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation